2018
DOI: 10.1097/ccm.0000000000003434
|View full text |Cite
|
Sign up to set email alerts
|

Meaning of Intracranial Pressure-to-Blood Pressure Fisher-Transformed Pearson Correlation–Derived Optimal Cerebral Perfusion Pressure: Testing Empiric Utility in a Mechanistic Model

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Akhondi-Asl et al stated that the PRx could only be evaluated when there are slow, but sufficient changes in ICP and ABP waves. This shows the sensitivity of the PRx calculation to slow wave changes, and only slight PRx variance can be seen with small slow wave changes [21]. In other words, if there are higher or lower wave changes in ABP(t) and ICP(t), the diagnostic PRx value would be different.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Akhondi-Asl et al stated that the PRx could only be evaluated when there are slow, but sufficient changes in ICP and ABP waves. This shows the sensitivity of the PRx calculation to slow wave changes, and only slight PRx variance can be seen with small slow wave changes [21]. In other words, if there are higher or lower wave changes in ABP(t) and ICP(t), the diagnostic PRx value would be different.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, a recent study by Akhondi-Asl et al [21] found that PRx can only be evaluated when there are slow, but sufficient changes in ABP(t) and ICP(t) waves. The results revealed the sensitivity of the PRx calculation towards small slow wave changes in ABP(t) and ICP(t), and only slight PRx variance was observed [21], which indicated that if ABP(t) and ICP(t) waves changed with a filtering approach, the diagnostic value of the PRx may change.…”
Section: Introductionmentioning
confidence: 99%
“…However, hypocapnia does not directly reduce ICP by reducing blood vessel volume but indirectly reduces blood vessel volume by decreasing CBF. 9 …”
Section: Arbon D Ioxide In S mentioning
confidence: 99%
“…Remarkably, the clinical utility of ICP monitoring for severe TBI in both children and adults is controversial [4,5]. Though attempts have been made to develop computational tools to enrich the utility of ICP monitoring data [6,7], there exists no widely accepted bedside tool to inform a proactive approach to management of severe TBI and treatment decisions remain largely reactive or empirical. Methodology that would guide individualized application of therapies to prevent ICP from exceeding threshold, optimize cerebral perfusion, prevent catastrophic herniation, and facilitate initiation, titration and weaning of therapies/ interventions would stand to significantly improve neurological outcomes.…”
Section: Introductionmentioning
confidence: 99%